2020
DOI: 10.1186/s12870-020-02691-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and comparative analysis of diacylglycerol kinase (DGK) gene family and their expression profiling in Brassica napus under abiotic stress

Abstract: Background Diacylglycerol kinases (DGKs) are signaling enzymes that play pivotal roles in response to abiotic and biotic stresses by phosphorylating diacylglycerol (DAG) to form phosphatidic acid (PA). However, no comprehensive analysis of the DGK gene family had previously been reported in B. napus and its diploid progenitors (B. rapa and B. oleracea). Results In present study, we identified 21, 10, and 11 DGK genes from B. napus, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Diverse gene function is affected significantly by the cis-element located in the promoter regions. Previous studies have reported that cis-elements on the promoters of DGKs are associated with multiple stresses such as drought, cold stress and wound stress and hormone responses such as ABA, SA and MeJA [16][17][18]21,22]. Some of the predictions were confirmed by the expression analysis.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Diverse gene function is affected significantly by the cis-element located in the promoter regions. Previous studies have reported that cis-elements on the promoters of DGKs are associated with multiple stresses such as drought, cold stress and wound stress and hormone responses such as ABA, SA and MeJA [16][17][18]21,22]. Some of the predictions were confirmed by the expression analysis.…”
Section: Discussionmentioning
confidence: 59%
“…In this study, we identified 18 AvDGK members within the Actinidia valvata genome which were located on 18 different chromosomes. The number of AvDGK genes identified in Actinidia valvata genome was relatively higher than the number found in Arabidopsis thaliana (7 AtDGKs) [14], in Zea mays (7 ZmDGKs) [21], in Malus domestica (8 MdDGKs) [19] and in Populus trichocarpa (7 PtDGKs) [22], but less than those in Triticum aestivum (24 TaDGKs) [18] and in Brassica napus (21 BnaDGKs) [17], which may be due to the differences in the size of the genome. The AvDGKs encoded proteins ranging from 456~734 amino acids, and these proteins were subcellularly located in the nucleus, chloroplast and cytoplasm.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Thus, PhDGK1 is the same type of enzyme as DGK2 and DGK7, which are known to be involved in plant growth and development. For example, MpDGK2 from Malus prunifolia was shown to affect the growth and tolerance of Arabidopsis via regulating H 2 O 2 homeostasis and antioxidant enzyme activity ( Tang et al, 2020 ). In addition, the content of PA, an important signaling molecule, was decreased in an AtDGK2- knockdown mutant, resulting in deceased pollen viability and pollen germination ( Angkawijaya et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…PA is produced through the phosphorylation of DAG or the hydrolysis of phospholipids and its synthesis can be induced by many types of stresses including chilling, freezing, drought and salinity [15,[53][54][55]. According to the maintenance of other lipid classes, the accumulation of PA in the plants subjected to D3 treatment may have resulted from the conversion of DAG, whose levels were also enhanced in this treatment [56]. As DAG can be further phosphorylated by DAG kinases to generate PA [57], its role in plants remains elusive [43].…”
Section: Discussionmentioning
confidence: 99%